Zirconium oxide composition, zirconium oxide calcined body and zirconium oxide sintered body, and methods for producing the same

Through the combination of zirconia materials with a specific particle size and stabilizer, combined with short-term sintering and preburning technology, the problems of insufficient shielding properties of zirconia dental materials and difficult to process the sintered body strength are solved, achieving high efficiency and low cost Dental repair production.

CN114650967BActive Publication Date: 2024-12-13KURARAY NORITAKE DENTAL
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080080453.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-22
Filing Date
2020-11-20
Publication Date
2024-12-13
Estimated Expiration
2040-11-20

AI Technical Summary

Technical Problem

The existing zirconia dental materials have insufficient shielding properties, high strength of sintered bodies and difficult to mechanically process, long firing time leads to low production efficiency and high energy costs, and patients cannot use patches on the same day.

Method used

The zirconia powder with a specific average particle size is combined with a yttrium stabilizer to prepare zirconia sintered bodies through short-time sintering technology to ensure high shielding and color development effect, and optimize the forming process through pre-sintering technology.

Benefits of technology

The manufacturing time of zirconia sintered bodies is shortened, production efficiency is improved, energy costs are reduced, and zirconia dental repairs can be used on the same day, with good shading effect and color rendering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0005089028670000011
    Figure FDA0005089028670000011
  • Figure 599713DEST_PATH_IMAGE004
    Figure 599713DEST_PATH_IMAGE004
Patent Text Reader

Abstract

The present invention provides a zirconium oxide composition and a pre-fired body capable of shortening the firing time when manufacturing a zirconium oxide sintered body, and capable of producing a zirconium oxide sintered body having high shielding properties and good color development. The present invention is a zirconium oxide composition, which contains a zirconium oxide powder and a stabilizer capable of inhibiting the phase transformation of the zirconium oxide powder, and satisfies all of the following (1) to (3). (1) The zirconium oxide powder contains zirconium oxide particles having an average particle size greater than 0.17 μm and less than 0.4 μm. (2) At least a portion of the stabilizer is not dissolved in the zirconium oxide. (3) When the composition is fired at 1300 to 1600°C, the chroma C of the sintered body when maintained at the above temperature for 30 minutes is * (30) and the chromaticity C of the sintered body when kept at the above temperature for 120 minutes * (120) ratio C * (30) / C * (120) is greater than 0.4.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a composition mainly containing zirconium oxide (zirconium dioxide (IV); ZrO2). In addition, the present disclosure relates to a calcined body and a sintered body of zirconium oxide. Furthermore, the present disclosure relates to a method for producing a zirconium oxide composition, a calcined body and a sintered body. Background Art

[0002] Zirconia is a compound that undergoes phase transitions between multiple crystal systems. Therefore, partially stabilized zirconia (PSZ; Partially-Stabilized Zirconia) and fully stabilized zirconia, which suppress phase transitions by dissolving stabilizers such as yttria (yttrium trioxide; Y2O3) in zirconia, are used in various fields. For example, Patent Document 1 discloses a partially stabilized zirconia sintered body for use in dental materials.

[0003] The translucent zirconia sintered body described in Patent Document 1 is produced by sintering a pressed body of zirconia powder at 1450°C, a heating rate of 300°C / hr, and a holding time of 2 hours. The zirconia powder contains 2 to 4 mol% of yttrium oxide and 0.1 to 0.2 wt% of aluminum oxide, and has a BET specific surface area of ​​5 to 15 m 2 / g, and the average particle size is 0.3~0.7μm.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2009-269812. Summary of the invention

[0007] Problems to be solved by the invention

[0008] One use of zirconium oxide as a dental material is to form a tooth to be a bridge abutment by cutting a carious site, and use a zirconium oxide crown processed in a manner that matches the abutment tooth. When the abutment tooth changes color due to a lesion or lifestyle, the zirconium oxide crown is required to have a certain degree of low light transmittance (high shielding property) in order to conceal the color of the discolored abutment tooth, but the shielding property of zirconium oxide described in Patent Document 1 is insufficient.

[0009] In addition, the zirconia sintered body obtained by sintering the zirconia particles (powder) is generally high in strength, so it is not easy to directly machine the zirconia sintered body into a desired shape. Therefore, the forming of the zirconia sintered body is sometimes carried out in the state of a pre-calcined body in which a pressurized compact of the zirconia powder (including a compact subjected to CIP (Cold Isostatic Pressing) treatment) is sintered at a temperature at which no sintering occurs (hereinafter referred to as "pre-calcination") to achieve agglomeration. In this case, the agglomerate of the zirconia pre-calcined body is formed into a desired shape by cutting or the like, and a zirconia sintered body having a target shape is produced by sintering the formed pre-calcined body at a temperature above which sintering is possible. In particular, as a dental material, a zirconia sintered body containing a colorant is produced in order to form a color similar to that of natural teeth.

[0010] When the pressed body of zirconium oxide powder is fired, it shrinks according to the firing temperature. For example, when the pressed body is fired to form a calcined body, it shrinks by about 1%, and when it is formed into a sintered body, it shrinks by about 20%. Therefore, in the forming of the calcined body, these shrinkage rates are taken into consideration, and the size of the sintered body to be the final target is formed larger than that of the sintered body. For example, the size of the formed calcined body is determined by a coefficient calculated by subtracting the shrinkage rate from the pressed body to the calcined body from the shrinkage rate from the pressed body to the sintered body.

[0011] Therefore, when multiple pressurized compacts are fired in one firing furnace to produce multiple pre-fired bodies (agglomerated bodies), it is desired to produce a zirconium oxide composition in which the shrinkage rate from the pressurized compacts to the formation of the pre-fired bodies among the multiple products is not easily affected by the temperature difference (temperature unevenness) generated in the firing furnace when producing the pre-fired bodies.

[0012] In addition, in the method for manufacturing a zirconia sintered body described in Patent Document 1, the holding time at the maximum firing temperature reaches 2 hours. Such long firing reduces production efficiency and increases energy costs. In addition, when a dental restoration is made of a zirconia sintered body, for example, the patient cannot be treated with the restoration on the day of treatment, and must go to the hospital again on another day to be treated with the restoration. On the other hand, for the zirconia powder described in Patent Document 1, if the holding time at the maximum firing temperature is shortened, white turbidity occurs and color development is reduced.

[0013] Therefore, there is a demand for a zirconia composition and a calcined body that can shorten the firing time when producing a zirconia sintered body and produce a zirconia sintered body having high shielding properties and good color development.

[0014] Means used to solve problems

[0015] The present inventors have repeatedly conducted intensive studies to solve the above-mentioned problems and have found that the above-mentioned problems can be solved by preparing a zirconium oxide composition having a specific crystal system, a specific average particle size of zirconium oxide particles, and exhibiting a specific chromaticity when fired. Based on this finding, the present inventors have conducted studies and completed the present invention.

[0016] That is, the present invention includes the following aspects.

[0017] [1] A zirconium oxide composition comprising a zirconium oxide powder and a stabilizer capable of suppressing phase transformation of the zirconium oxide powder, and satisfying all of the following (1) to (3).

[0018] (1) The zirconium oxide powder contains zirconium oxide particles having an average particle size of more than 0.17 μm and not more than 0.4 μm.

[0019] (2) At least a portion of the stabilizer is not dissolved in zirconium oxide.

[0020] (3) When the composition is fired at 1300-1600°C, the chromaticity C of the sintered body when kept at the above temperature for 30 minutes is * (30) and the chromaticity C of the sintered body when kept at the above temperature for 120 minutes * (120) ratio C * (30) / C * (120) is greater than 0.4.

[0021] [2] The zirconium oxide composition according to [1], wherein the monoclinic crystal system in the crystal system of the zirconium oxide accounts for 55% or more.

[0022] [3] The zirconium oxide composition according to [1] or [2], wherein the stabilizer is yttrium oxide.

[0023] [4] The zirconium oxide composition according to [3], comprising 3 to 7.5 mol % of yttrium oxide based on the total molar amount of zirconium oxide and yttrium oxide.

[0024] [5] The zirconium oxide composition according to [3] or [4], wherein a peak of yttrium oxide is present in the X-ray diffraction pattern.

[0025] [6] The zirconium oxide composition according to any one of [3] to [5], wherein the abundance ratio f of yttrium oxide not dissolved in zirconium oxide calculated according to the following mathematical formula (i) is: y More than 1%.

[0026] [Mathematical formula 1]

[0027]

[0028] (Among them, I y (111) represents the peak intensity of the (111) plane of yttrium oxide at around 2θ=29° in the X-ray diffraction pattern using CuKα rays;

[0029] I m (111) and I m (11-1) represents the peak intensity of the (111) plane and the (11-1) plane of the monoclinic system of zirconium oxide in the aforementioned X-ray diffraction pattern;

[0030] I t (111) represents the peak intensity of the (111) plane of the tetragonal system of zirconium oxide in the aforementioned X-ray diffraction pattern;

[0031] I c (111) represents the peak intensity of the (111) plane of the cubic crystal system of zirconium oxide in the aforementioned X-ray diffraction pattern).

[0032] [7] The zirconium oxide composition according to [6], wherein the above-mentioned f y Less than 15%.

[0033] [8] The zirconium oxide composition according to any one of [1] to [7], wherein the chromaticity C of the sintered body when kept at the above temperature for 30 minutes is * (30) is 3 or more.

[0034] [9] The zirconium oxide composition according to any one of [1] to [8], wherein the light transmittance of a sintered body obtained by sintering at a maximum sintering temperature of 1300 to 1600° C. satisfies the following formula.

[0035] ΔL * (WB)≤11

[0036] (Where ΔL * (WB) is the first L * Value minus the second L * The value obtained by the first L * The value is L measured with the background of the sintered body of 1.2 mm thickness set to white. * Value, second L * The value will be determined for the first L * The L value of the same sintered body is measured with the background set to black. * Value, L * The value is L * a * b * L of chroma (color space) in the color system (JIS Z 8781-4:2013) * value).

[0037]

[10] The zirconium oxide composition according to [9], wherein the light transmittance ΔL when kept at the above temperature for 30 minutes is * (30) and the light transmittance ΔL when kept at the above temperature for 120 minutes * (120) ratio ΔL * (30) / ΔL * (120) is greater than 0.88.

[0038]

[11] A method for producing a calcined zirconium oxide body, comprising producing the calcined zirconium oxide body using the zirconium oxide composition described in any one of [1] to

[10] .

[0039]

[12] The method for producing a calcined zirconium oxide body according to

[11] , wherein the calcined body is produced by calcining the pressed body comprising the zirconium oxide composition according to any one of [1] to

[10] at 800 to 1200°C.

[0040]

[13] The method for producing a zirconia calcined body according to

[11] or

[12] , comprising:

[0041] A first molding step of molding a zirconium oxide composition comprising a zirconium oxide powder and a stabilizer capable of inhibiting phase transformation of the zirconium oxide powder as described in any one of [1] to

[10] to produce a first molded body; and

[0042] The first molded body is sintered at a temperature at which the zirconium oxide particles are not sintered.

[0043]

[14] The method for producing a zirconia calcined body according to

[13] , wherein in the calcining step, the first formed body is calcined at 800 to 1200°C.

[0044]

[15] The method for producing a zirconia calcined body according to

[13] or

[14] , wherein, before the first forming step, it further includes: a pulverizing step of pulverizing a mixture of the zirconia powder and the stabilizer to obtain a zirconia composition in a manner such that the zirconia powder contains zirconia particles having an average particle size greater than 0.17 μm and less than 0.4 μm.

[0045]

[16] The method for producing a zirconia calcined body according to any one of

[13] to

[15] , further comprising, before the first forming step, a drying step of forming the zirconium oxide composition into particles by spray drying.

[0046]

[17] The method for producing a zirconia calcined body according to any one of

[11] to

[16] , wherein the density of the zirconia calcined body is 2.7 to 4.0 g / cm 3 .

[0047]

[18] The method for producing a zirconia calcined body according to any one of

[11] to

[17] , wherein the zirconia calcined body has a flexural strength of 15 to 70 MPa as measured in accordance with ISO 6872:2015.

[0048]

[19] A method for producing a zirconia sintered body, comprising:

[0049] A first molding step of molding the zirconium oxide composition described in any one of [1] to

[10] to produce a first molded body; and

[0050] The sintering step is to sinter the first compact at a temperature higher than a sinterable temperature.

[0051]

[20] The method for manufacturing a zirconia sintered body according to

[19] , wherein, before the aforementioned sintering step, it also includes: a pre-firing step of sintering the aforementioned first formed body at a temperature at which the zirconia particles do not sinter to produce a zirconia pre-firing body, and in the aforementioned sintering step, the aforementioned zirconia pre-firing body is sintered as the aforementioned first formed body.

[0052]

[21] The method for producing a zirconia sintered body according to

[20] , further comprising, before the sintering step, a second forming step of forming the zirconia calcined body to produce a second formed body,

[0053] In the sintering step, the second compact is sintered.

[0054]

[22] The method for producing a zirconia sintered body according to any one of

[19] to

[21] , wherein in the sintering step, the holding time at the maximum sintering temperature is 1 hour or less.

[0055] Effects of the Invention

[0056] According to the present disclosure, it is possible to shorten the manufacturing time of the sintered body and produce a zirconia sintered body with high hiding power and good color development. As a result, the production efficiency of the product can be improved and the energy cost can be reduced. When the zirconia sintered body is applied to dental restorations, the time burden on the patient can be reduced. In addition, according to the present disclosure, due to the excellent hiding power, the color of the discolored abutment teeth can be concealed. In the dental treatment of patients with abutment teeth that have been discolored due to lesions or lifestyle habits, the zirconia sintered body can be suitably used as a dental restoration. DETAILED DESCRIPTION

[0057] It is important that the zirconium oxide composition of the present disclosure contains zirconium oxide powder and a stabilizer capable of suppressing phase transformation of the zirconium oxide powder, and satisfies all of the following (1) to (3).

[0058] (1) The zirconium oxide powder contains zirconium oxide particles having an average particle size of more than 0.17 μm and not more than 0.4 μm.

[0059] (2) At least a portion of the stabilizer is not dissolved in zirconium oxide.

[0060] (3) When the composition is sintered at 1300-1600°C, the ratio C*(30) / C*(120) of the chroma C*(30) of the sintered body when kept at the above temperature for 30 minutes to the chroma C*(120) of the sintered body when kept at the above temperature for 120 minutes is 0.4 or more.

[0061] First, the zirconium oxide composition of the present disclosure will be described. The zirconium oxide composition of the present disclosure can be a precursor (intermediate product) of a zirconium oxide sintered body and a calcined body.

[0062] The zirconium oxide composition disclosed herein contains zirconium oxide powder and a stabilizer capable of inhibiting the phase change of zirconium oxide. The stabilizer is preferably a stabilizer capable of forming partially stabilized zirconium oxide. Examples of the stabilizer include calcium oxide (CaO), magnesium oxide (MgO), yttrium oxide (yttrium trioxide; Y2O3), cerium oxide (CeO2), scandium oxide (Sc2O3), lanthanum oxide (La2O3), erbium oxide (Er2O3), praseodymium oxide (Pr6O3), and vanadium oxide (Er2O3). 11 ), samarium oxide (Sm2O3), europium oxide (Eu2O3) and thulium oxide (Tm2O3) etc. The content of stabilizer in zirconium oxide composition, calcined body and sintered body can be measured by, for example, inductively coupled plasma (ICP) emission spectrometry, fluorescent X-ray analysis and the like.

[0063] In the zirconium oxide composition disclosed herein, the chromaticity C of the zirconium oxide sintered body when fired for a short time is *From the point of view of the invention, it is important that the stabilizer exists in a monoclinic system in at least a part of the zirconium oxide crystals, that is, at least a part of the stabilizer is not dissolved in the zirconium oxide. That a part of the stabilizer is not dissolved in the zirconium oxide can be confirmed by, for example, an X-ray diffraction (XRD; X-Ray Diffraction) pattern. When a peak derived from the stabilizer is confirmed in the XRD pattern of the zirconium oxide composition, there is a stabilizer that is not dissolved in the zirconium oxide in the zirconium oxide composition. In the case where the entire amount of the stabilizer is dissolved, basically no peak derived from the stabilizer is confirmed in the XRD pattern. Among them, depending on conditions such as the crystal state of the stabilizer, even if there is no peak of the stabilizer in the XRD pattern, the stabilizer is sometimes not dissolved in the zirconium oxide. When the main crystal system of zirconium oxide is the tetragonal system and / or the cubic system, and there is no peak of the stabilizer in the XRD pattern, it can be considered that most of the stabilizer, basically all of it, is dissolved in the zirconium oxide.

[0064] From the viewpoint of the strength and shielding property of the zirconium oxide sintered body made from the zirconium oxide composition disclosed in the present invention, the stabilizer is preferably yttrium oxide. The content of yttrium oxide is preferably 3 mol% or more relative to the total mole of zirconium oxide and yttrium oxide. From the viewpoint that the color of the discolored abutment teeth can be fully shielded when combined with zirconium oxide powder having a specified average particle size and the shielding property is more excellent, it is more preferably 3.3 mol% or more, and further preferably 3.5 mol% or more. When the content of yttrium oxide is 3 mol% or more, the phase transformation of the zirconium oxide sintered body can be suppressed. In addition, the content of yttrium oxide is preferably 7.5 mol% or less, more preferably 7 mol% or less, further preferably 6.5 mol% or less, and particularly preferably 6 mol% or less relative to the total mole of zirconium oxide and yttrium oxide. When the content of yttrium oxide is 7.5 mol% or less, the reduction in the strength of the zirconium oxide sintered body can be suppressed.

[0065] The existence ratio f of yttrium oxide not dissolved in zirconium oxide (hereinafter referred to as "undissolved yttrium oxide") in the zirconium oxide composition of the present disclosure is y It can be calculated according to the following mathematical formula (i). The existence rate of undissolved yttrium oxide f y It is preferably greater than 0%, more preferably 1% or more, further preferably 2% or more, and further preferably 3% or more. y The preferred upper limit of depends on the content of yttrium oxide in the zirconium oxide composition. When the content of yttrium oxide is 7.5 mol% or less relative to the total molar amount of zirconium oxide and yttrium oxide, from the perspective of short calcination time, f y For example, when the content of yttrium oxide is 3.5 mol% or more and 4.5 mol% or less, f y When the content of yttrium oxide exceeds 4.5 mol % and is 6 mol % or less, fy When the content of yttrium oxide exceeds 6 mol % and is 7.5 mol % or less, f y It can be set below 11%.

[0066] [Mathematical formula 2]

[0067]

[0068] In the above mathematical formula (i), I y (111) represents the peak intensity of the (111) plane of yttrium oxide near 2θ=29° in the XRD pattern using CuKα radiation. m (111) and I m (11-1) represents the peak intensity of the (111) plane and the (11-1) plane of the monoclinic system of zirconium oxide. t (111) represents the peak intensity of the (111) plane of the tetragonal system of zirconium oxide. c (111) represents the peak intensity of the (111) plane of the cubic crystal system of zirconium oxide.

[0069] The above mathematical formula (i) is replaced by other peaks. y (111) can also be used to calculate the existence rate of the undissolved form of stabilizers other than yttrium oxide.

[0070] The main crystal system of zirconium oxide in the zirconium oxide composition of the present disclosure is preferably monoclinic. In the present disclosure, "the main crystal system is monoclinic" means that the proportion of monoclinic in zirconium oxide is calculated by the following mathematical formula (ii) based on the XRD peak using CuKα rays relative to the total amount of all crystal systems (monoclinic, tetragonal and cubic) in zirconium oxide: m It should be noted that the meanings of the symbols in the mathematical formula (ii) are the same as those in the mathematical formula (i). In the zirconium oxide composition of the present invention, the proportion of monoclinic crystals in zirconium oxide is m It is preferably 55% or more, more preferably 60% or more, further preferably 70% or more, further preferably 80% or more, particularly preferably 90% or more, and most preferably 95% or more. The main crystal system in the zirconium oxide composition may contribute to the increase in the speed change temperature and the shortening of the sintering time.

[0071] [Mathematical formula 3]

[0072]

[0073] The zirconium oxide composition disclosed herein contains zirconium oxide powder. In the present disclosure, the powder may be an aggregate of particles. The particles are obtained by aggregating primary particles and / or secondary particles formed by aggregating primary particles.

[0074] The "primary particle" in the present disclosure refers to a particle of a spherical body in the smallest unit. For example, a primary particle refers to a spherical body in which the particles appear to be unbound and separable under an electron microscope (e.g., a scanning electron microscope). The "secondary particle" mentioned in the present disclosure refers to a particle in which particles that appear to be primary particles under an electron microscope are aggregated. Secondary particles also include aggregates formed by primary particles attached in a form that can be broken apart and aggregates formed by primary particles fused in an inseparable form to appear to form one particle. In most cases, secondary particles do not form a spherical body in an electron microscope image and have a deformed shape.

[0075] The particles constituting the particles are preferably primary particles as the main body. For example, in the visual confirmation of the electron microscope image, the number of primary particles is preferably more than the number of secondary particles. For example, in the visual confirmation of the electron microscope image, among the primary particles (including the primary particles constituting the secondary particles), preferably more than 50%, more preferably more than 70%, and further preferably more than 80% of the primary particles are particles that do not constitute secondary particles. Secondary particles generally present irregular shapes, therefore, if the secondary particles become more, the circularity of the particles described later becomes low.

[0076] It is important that the average particle size of the zirconium oxide particles in the present disclosure exceeds 0.17 μm, preferably 0.18 μm or more, and more preferably 0.19 μm or more, when measured by a laser diffraction / scattering particle size distribution measurement method. The zirconium oxide powder has excellent shielding properties by containing zirconium oxide particles having an average particle size exceeding 0.17 μm. In addition, when the zirconium oxide powder is only zirconium oxide particles having an average particle size of less than 0.17 μm, the shielding properties become insufficient. In addition, it is important that the average particle size is less than 0.40 μm, preferably less than 0.35 μm, and more preferably less than 0.30 μm. If it exceeds 0.40 μm, there is a possibility of insufficient strength. The "average particle size of the zirconium oxide particles" in the present disclosure refers to the particle size measured without distinguishing between primary particles and secondary particles. In a suitable embodiment, the "average particle size of the zirconium oxide particles" refers to primary particles. In other suitable embodiments, the "average particle size of the zirconium oxide particles" refers to secondary particles. In addition, when the zirconium oxide powder is a particle, it refers to the average particle size of the particles constituting the particle. The laser diffraction scattering method can be measured on a volume basis using, for example, a laser diffraction particle size distribution measuring apparatus (such as "SALD-2300" manufactured by Shimadzu Corporation) using ethanol or a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium.

[0077] The BET specific surface area of ​​the zirconium oxide powder in the present disclosure is preferably 7.0 m 2 / g or more, more preferably 7.5m 2 / g or more, more preferably 8m 2 / g or more. Less than 7.0m 2 / g, it is difficult to sinter or even if it can be sintered, the sintered body will be turbid. In addition, the BET specific surface area is preferably 30m 2 / g or less, more preferably 25m 2 / g or less, more preferably 20m 2 / g or less. If it exceeds 30m 2 / g, the speed change temperature described later becomes higher and is easily affected by the temperature unevenness in the sintering furnace. In addition, if the sintering time for sintering is shortened, the color development of the sintered body deteriorates. The BET specific surface area mentioned here refers to the specific surface area measured without distinguishing between primary particles and secondary particles.

[0078] In the zirconium oxide composition of the present disclosure, 50% or more, preferably 70% or more, more preferably 80% or more, and even more preferably 90% or more of the zirconium oxide powder may be in the form of particles.

[0079] In an embodiment in which the average particle size of the zirconium oxide particles is a primary particle, the average particle size of the particles (secondary particles) in the zirconium oxide composition disclosed in the present invention is preferably 10 μm or more, more preferably 12 μm or more, and further preferably 14 μm or more. When the average particle size of the particles is less than 10 μm, it is possible that air is trapped when the particles are loaded into the mold, and degassing becomes insufficient during molding, and a uniform and dense molded body cannot be produced. In addition, it is possible that particles are ejected from the gap during molding to produce a molded body that does not meet the required amount. The average particle size of the particles is preferably less than 200 μm, more preferably less than 190 μm, further preferably less than 180 μm, further preferably less than 150 μm, and particularly preferably less than 100 μm. If the average particle size of the particles exceeds 200 μm, it is easy to form cavities inside the particles. In addition, gaps are easily generated when the particles are loaded into the mold. Due to these phenomena, degassing may become insufficient during molding, and a dense molded body cannot be produced. In addition, it is possible that shrinkage becomes larger during molding, and a molded body of the desired size cannot be produced. In the present disclosure, the average particle size of the particles is preferably measured by a method in which the particles are not destroyed. The average particle size of the particles can be measured by, for example, a dry screening method or a wet screening method. The dry screening method can be measured according to the screening test method described in JIS Z 8815:1994, and manual screening and mechanical screening can be used, preferably mechanical screening. As the sieve used in the screening method, the sieve described in JIS Z 8801-1:2019 Test Sieve can be used. As a measuring device used in the screening method, for example, an RO-TAP type vibrating screen or a sonic vibration type screening measuring device can be used for measurement. As an RO-TAP type vibrating screen, for example, "RPS-105M" manufactured by Seishin Enterprise Co., Ltd. can be listed. Examples of the sonic vibration type sieve measuring device include “Robotron Scale RPS-01” and “Robotron Scale RPS-02” manufactured by Seishin Enterprises.

[0080] The particles in the zirconium oxide composition of the present invention preferably have a high sphericity. By increasing the sphericity of the particles, mixing at the interlayer interface can be induced when zirconium oxide powders of different compositions are stacked. In addition, when the zirconium oxide powder is filled into a mold to make a molded body, even if the average particle size is the same, a high sphericity can increase the packing density. By filling zirconium oxide powder or zirconium oxide particles into a specific mold (metal mold, etc.) and increasing the density of the molded body made into a specific shape by pressure, that is, the packing density, the strength of the sintered body can be improved. In addition, even in the case where the mold has corners, the filling property of the particles filled in the corners can be improved. The sphericity of the particles can be expressed by, for example, circularity, angle of repose, light packing density, heavy packing density, etc. based on a projected image.

[0081] The average circularity of the particles in the zirconium oxide composition disclosed herein based on the projected image is preferably 0.81 or more, more preferably 0.85 or more, further preferably 0.90 or more, and further preferably 0.95 or more. The circularity can be calculated as the ratio of the circumference of a circle equal to the area of ​​the particle in the projected image to the circumference of the particle. That is, the circularity can be calculated by the following formula. The average circularity is preferably set to the average circularity of more than 10,000 particles.

[0082] Circularity = (circumference of a circle equal to the area of ​​the particle (circumference)) / circumference of the particle

[0083] The repose angle of the zirconium oxide composition disclosed herein is preferably 35° or less, more preferably 32° or less, further preferably 28° or less, further preferably 26° or less, and particularly preferably 24° or less. The repose angle can be measured according to JIS R 9301-2-2:1999.

[0084] The light packing density of the zirconium oxide composition disclosed herein is preferably 1.0 g / cm 3 More preferably, 1.1 g / cm 3 More preferably, 1.2 g / cm 3 Above, particularly preferably 1.3 g / cm 3 The light bulk density can be measured according to JIS R9301-2-3:1999.

[0085] The repacking density of the zirconium oxide composition disclosed herein is preferably 1.3 g / cm 3 More preferably 1.4 g / cm 3 More preferably, 1.5 g / cm 3 The bulk density can be measured according to JIS R 9301-2-3:1999.

[0086] The zirconium oxide composition disclosed in the present invention may contain additives other than zirconium oxide powder and the aforementioned stabilizer. Examples of additives include colorants (including pigments, composite pigments, and fluorescent agents), binders, dispersants, defoamers, aluminum oxide (Al2O3), titanium oxide (TiO2), silicon dioxide (SiO2), and the like. One additive may be used alone or in combination of two or more. The target chroma C may be considered. * To appropriately set the content of these additives.

[0087] Examples of colorants include oxides of at least one element selected from Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, Tb, and Er (specifically, NiO, Cr2O3, etc.). Examples of composite pigments include composite oxides such as (Zr, V) O2, Fe(Fe, Cr) 2 O4, (Ni, Co, Fe) (Fe, Cr) 2 O4・ZrSiO4, and (Co, Zn) Al2 O4. Examples of fluorescent agents include Y2SiO5:Ce, Y2SiO5:Tb, (Y, Gd, Eu) BO3, Y2O3:Eu, YAG:Ce, ZnGa2O4:Zn, BaMgAl 10 O 17 :Eu et al.

[0088] Examples of the binder include organic binders, such as acrylic binders, paraffin binders, fatty acid binders, and polyvinyl alcohol binders.

[0089] The zirconium oxide composition disclosed herein may be in a dry state, or may be in a state containing a liquid or in a state contained in a liquid. For example, the zirconium oxide composition may be in a powdery, paste-like, slurry-like form, etc. In addition, the zirconium oxide composition may be a molded body having a predetermined shape (hereinafter referred to as a "first molded body").

[0090] The density of the first molded body is preferably 2.75 g / cm 3 More preferably, 2.80 g / cm 3 More preferably, 2.85 g / cm 3 More preferably, it is 2.90 g / cm 3 More than 3.00 g / cm 3 The density can be calculated, for example, in the form of (mass of the first compact) / (volume of the first compact).

[0091] In the present disclosure, the color development degree of the zirconia sintered body can be expressed by the chroma C * It is shown that when the zirconium oxide composition of the present invention is fired at 1300-1600°C, the chroma C * It is preferably 3 or more, more preferably 5 or more, and even more preferably 7 or more. The chroma C in the present invention * It means L * a * b * C of chroma (color space) in the color system (JIS Z 8781-4:2013) * The value can be measured by setting the background of a sample of a zirconia sintered body with a thickness of 1.2 mm to black.* Value and b * The value is calculated using the mathematical formula (iii). It should be noted that the chromaticity C when firing is preferably performed at at least one temperature in the range of 1300 to 1600°C. * Satisfy the above range.

[0092] C * ={(a * ) 2 +(b * ) 2} (1 / 2) (iii)

[0093] Regarding the method for preparing the sample, first, the zirconium oxide composition (e.g., particles) can be press-formed in such a way that the thickness of the zirconium oxide sintered body reaches 1.2 mm, and then, a circular plate-shaped formed body with a diameter of 19 mm can be prepared by CIP forming. Then, the formed body can be sintered under predetermined sintering conditions to prepare a zirconium oxide sintered body with a thickness of 1.2 mm as a sample. * Value and b * The value can be measured by applying the contact liquid on the surface of the sample and then using a colorimeter (e.g., dental colorimeter "Crystalline CE100-DC / JP" (manufactured by Orinpass Co., Ltd.), analysis software "Crystalline" (manufactured by Orinpass Co., Ltd.)) to measure the a value of the black background. * Value and b * The black background refers to the black portion of the shielding test paper described in JIS K 5600-4-1:1999, Part 4, Section 1. As the contact liquid, for example, a liquid having a refractive index nD of 1.60 measured at a measurement wavelength of 589 nm (sodium D-ray) can be used.

[0094] The zirconium oxide composition of the present invention exhibits good color development even under short-time calcination, and can obtain a desired chromaticity C * As an indicator for determining whether sintering can be performed in a short time, the C at each holding time x and y can be calculated. * The ratio = C * (x) / C * (y) (x≤y, unit: minutes). It is important that when the zirconium oxide composition of the present invention is fired at a maximum firing temperature of 1300-1600°C, the chromaticity C of the sintered body when kept at the above temperature for 30 minutes is * (30) and the chromaticity C of the sintered body when kept at the above temperature for 120 minutes * (120) ratio C * (30) / C *(120) is 0.4 or more, preferably 0.6 or more, more preferably 0.8 or more, further preferably 0.9 or more, and particularly preferably 0.93 or more. * (30) / C * When (120) is less than 0.4, the color development is poor during short-time firing, and the desired chroma C cannot be obtained. * It should be noted that the important thing is that the chroma ratio C when fired at at least one specific temperature within the range of 1300~1600℃ is * (30) / C * (120) satisfies the above range.

[0095] It should be noted that the chroma C of the present disclosure is measured * When using the above-mentioned zirconium oxide composition, instead of using a sample which is directly sintered by sintering at a temperature in the range of 1300-1600°C to form a sintered state, a sample which has undergone a pre-sintering state, for example, a sample which is first sintered at a temperature in the range of 800-1200°C to form a zirconium oxide pre-sintered body and then sintered at a temperature in the range of 1300-1600°C to obtain a zirconium oxide sintered body, can be used.

[0096] An advantage of the zirconium oxide composition of the present invention is described below. Generally speaking, the shrinkage rate from the pressurized molded body of zirconium oxide to the sintered body is not constant relative to the firing temperature. The shrinkage rate is low until a certain temperature, but the shrinkage rate at the certain temperature becomes higher. The temperature at which the shrinkage rate changes is expressed as a "speed change temperature" in the present disclosure. According to the zirconium oxide composition of the present disclosure, the speed change temperature can be set to 1050°C or more, preferably 1100°C or more.

[0097] As a batch, when multiple pressurized compacts are fired simultaneously in a firing furnace to produce multiple pre-burned bodies (agglomerated bodies), among multiple pressurized compacts, the deviation of the shrinkage rate until the pre-burned body is preferably small. If the deviation of the shrinkage rate is large, when the pre-burned body is formed, if the same coefficient is applied to the batch to determine the size of the formed body, a zirconia sintered body without a target size is obtained. This is particularly problematic in the case of products requiring high dimensional accuracy such as dental restorations. Therefore, agglomerated bodies whose shrinkage rate deviates from the acceptable range in a batch cannot be used as products, and the yield rate is reduced.

[0098] According to the zirconium oxide composition disclosed in the present invention, for the firing temperature (for example, about 1000°C) of the agglomerate body used to manufacture the zirconium oxide calcined body, the deviation of the shrinkage rate in one batch can be reduced. Generally, the highest firing temperature (hereinafter referred to as "pre-firing temperature") used to make the zirconium oxide calcined body is close to the speed change temperature. Generally, at the pre-firing temperature, a temperature difference (temperature unevenness) of about 20 to 50°C is generated in the sintering furnace. Therefore, when the speed change temperature is near the pre-firing temperature, the batch of the composition is significantly affected by the temperature unevenness. That is, in one batch, the shrinkage rate of the zirconium oxide calcined body at a low temperature position is significantly different from that of the zirconium oxide calcined body at a high temperature position. Since the zirconium oxide calcined body whose shrinkage rate deviates from the acceptable range cannot be made into a product, the yield rate is reduced. On the other hand, according to the zirconium oxide composition disclosed in the present invention, the speed change temperature can be increased, and the difference between the speed change temperature and the pre-firing temperature can be reduced. Therefore, in one batch, the difference in shrinkage rate between the zirconium oxide calcined body at a low temperature position and the zirconium oxide calcined body at a high temperature position can be reduced. As a result, the number of zirconia calcined bodies with shrinkage rates deviating from the acceptable range can be reduced, and the yield rate can be improved. In addition, the number of products that can be sintered at a time can be increased, and the production efficiency can be improved.

[0099] Specifically, when a press-formed body of a zirconium oxide composition is fired at 800°C to 1000°C to prepare a calcined body, the shrinkage rate from the press-formed body to the calcined body is preferably 1% or less relative to the size of the press-formed body in one direction. In addition, when a press-formed body of a zirconium oxide composition is fired at a temperature higher than 1000°C to 1200°C to prepare a zirconium oxide calcined body, the shrinkage rate from the press-formed body to the calcined body is preferably 5% or less relative to the size of the press-formed body in one direction. The press-formed body mentioned here is, for example, a zirconium oxide powder is pressed at a predetermined pressure (e.g., 300 kg / cm 2 The molded body obtained by pressure molding under 1700 kg / cm 2 ) and the resulting formed body.

[0100] Furthermore, the zirconia composition and the zirconia calcined body produced therefrom can produce a final product (zirconia sintered body) with high dimensional accuracy regardless of the aggregate in a batch. The zirconia composition and the zirconia calcined body are particularly useful in the production of products requiring high dimensional accuracy (e.g., dental products).

[0101] The zirconium oxide composition and zirconium oxide calcined body disclosed in the present invention have further advantages. According to the zirconium oxide composition and zirconium oxide calcined body disclosed in the present invention, the firing time for making the zirconium oxide sintered body can be shortened without reducing the strength of the produced zirconium oxide sintered body. In particular, the holding time at the highest firing temperature for making the zirconium oxide sintered body can be shortened (short-time firing). Thus, production efficiency can be improved and manufacturing costs can be reduced. When short-time firing is performed, the residence time of the zirconium oxide composition or the zirconium oxide calcined body in the firing furnace is preferably less than 60 minutes at the aforementioned highest firing temperature. In addition, when the zirconium oxide composition and the zirconium oxide calcined body disclosed in the present invention are applied to dental products, the time from determining the size of the dental product used in treatment to the time of treatment using the dental product can be shortened, which can reduce the time burden on patients.

[0102] Next, an example of a method for producing the zirconium oxide composition of the present disclosure will be described.

[0103] First, zirconium oxide powder and a stabilizer are mixed in a prescribed ratio to prepare a mixture (mixing process). For example, when the stabilizer is yttrium oxide, the mixing ratio can be set to be the same as the content of yttrium oxide in the aforementioned zirconium oxide composition. Mixing can be performed by dry method or wet method. By dispersing the mixture until the average particle size of the above-mentioned zirconium oxide particles is reached, and then crushing it as needed until the BET specific surface area of ​​the zirconium oxide powder is reached, the zirconium oxide composition disclosed in the present invention can be manufactured (first crushing process). It should be noted that the mixing process and the first crushing process can be carried out in the same process. Crushing can be carried out using a ball mill, for example, after the mixture is dispersed in a solvent such as water. In the method for manufacturing the zirconium oxide composition, without performing the process after the pre-sintering process described later, in order to increase the speed change temperature and / or sinter in a short time, the process of crushing the mixture in a manner that the zirconium oxide powder contains zirconium oxide particles having an average particle size greater than 0.17 μm and less than 0.4 μm is included. The average particle size can be measured by the laser diffraction / scattering particle size distribution measurement method as described above. After the mixing step and / or the first pulverizing step, the zirconium oxide composition may be dried by spray drying using a spray dryer or the like and formed into the above-mentioned particle form (first drying step). In this way, the zirconium oxide composition of the present invention can be produced.

[0104] The following steps can be arbitrarily implemented according to the purpose of use of the zirconium oxide composition. For example, after any of the above steps, the mixture and / or the zirconium oxide composition can be sintered (i.e., pre-sintered) at a temperature at which the zirconium oxide particles do not sinter (sintering (pre-sintering) step). The sintering conditions are preferably such that the main crystal system of zirconium oxide when cooled after sintering does not form a tetragonal system and a cubic system as described above. In addition, the sintering conditions are preferably such that at least a portion of the stabilizer does not dissolve in the zirconium oxide. For example, the sintering temperature is preferably above 700°C, more preferably above 800°C. In addition, the sintering temperature is preferably below 1200°C, more preferably below 1100°C, further preferably below 1000°C, further preferably below 980°C, and particularly preferably below 950°C. Firing can be carried out in the atmosphere. It can be considered that by performing a pre-sintering step, a portion of the stabilizer is dissolved in the zirconium oxide, or the stabilizer is easily dissolved in the subsequent sintering step, or the properties of the zirconium oxide sintered body can be improved.

[0105] After any of the above steps, the zirconium oxide composition can be dispersed in a solvent such as water to prepare a slurry, and additives such as a binder and a colorant can be added to the zirconium oxide composition (addition step). After the addition step, the zirconium oxide composition can be crushed until the average particle size of the zirconium oxide particles is reached, and then crushed as needed until the BET specific surface area of ​​the zirconium oxide powder is reached (second crushing step). It should be noted that the addition step and the second crushing step can be carried out in the same step. The second crushing step can be carried out in the same manner as the first crushing step. After the addition step and / or the second crushing step, the zirconium oxide composition can also be dried by spray drying using a spray dryer or the like, and the zirconium oxide composition can be formed into a particle form as described above (second drying step).

[0106] As described above, the zirconium oxide composition may also be formed into a first molded body (first molding step). The molding method is not limited to a specific method, and a suitable method may be appropriately selected according to the purpose. For example, the zirconium oxide composition may be formed by molding methods such as press molding, injection molding, and photoforming to form a first molded body. In addition, multi-step molding may also be performed. For example, after the zirconium oxide composition is press molded, a CIP treatment may be further performed.

[0107] In order to obtain the desired chroma C * The above-mentioned binders, colorants and other additives can be appropriately added in each process.

[0108] The zirconium oxide composition of the present invention can be produced by the above-mentioned production method. As a suitable production method of the zirconium oxide composition, there can be cited a production method that can produce the above-mentioned zirconium oxide composition with a high speed change temperature and / or a shortened sintering time for sintering. The shortening of the sintering time can be based on the presence ratio f of the above-mentioned undissolved yttrium oxide. y The adjustment can be made by adjusting or selecting the average particle size of the zirconium oxide powder, etc.

[0109] The zirconium oxide composition of the present disclosure can be used to suitably produce a zirconium oxide calcined body. In addition, the zirconium oxide composition of the present disclosure or a zirconium oxide calcined body produced from the zirconium oxide composition can be used to suitably produce a zirconium oxide sintered body. This will be described in detail below.

[0110] First, the zirconia calcined body of the present disclosure is described. The calcined body in the present disclosure can be a precursor (intermediate product) of a zirconia sintered body. In the present disclosure, the zirconia calcined body can be, for example, a product obtained by agglomerating zirconia particles (powder) in a state where they are not completely sintered. The density of the zirconia calcined body of the present disclosure is preferably 2.7 g / cm 3 In addition, the density is preferably 4.0 g / cm 3 Below, more preferably 3.8 g / cm 3 Below, more preferably 3.6 g / cm 3 Below. If the density of the zirconia calcined body is within this range, it can be easily formed. The density can be calculated, for example, in the form of (mass of the calcined body) / (volume of the calcined body). The density of the zirconia calcined body refers to the density of the calcined body obtained by filling the zirconia particles into a specific mold (metal mold, etc.), forming a specific shape with pressure, heating the resulting molded body at a temperature capable of removing the binder, and then heating the molded body at a temperature at which the yttrium oxide is just dissolved and a neck is just formed (bonded). The temperature when the aforementioned binder is removed is not particularly limited as long as it is a temperature at which the binder can be removed, and can be 150~500°C. The temperature at which the yttrium oxide is just dissolved and a neck is just formed (bonded) is not particularly limited, and can be 800~1050°C.

[0111] The preferred range of the content of the stabilizer in the zirconium oxide calcined body of the present disclosure is the same as that in the above-mentioned zirconium oxide composition. From the viewpoint of strength and light transmittance after sintering, the stabilizer is preferably yttrium oxide.

[0112] In the zirconia calcined body disclosed in the present invention, the stabilizer is preferably present in the form of monoclinic crystals in at least a portion of the zirconia crystals, that is, at least a portion of the stabilizer is not dissolved in the zirconia. The existence rate of the undissolved form of the stabilizer in the zirconia calcined body also depends on the firing temperature when the zirconia calcined body is produced, and it can generally be considered to be less than the existence rate in the zirconia composition before the zirconia calcined body is produced. The existence rate of undissolved yttrium oxide in the zirconia calcined body is f y The existence ratio of undissolved yttrium oxide in the calcined zirconium oxide body f can be calculated according to the above mathematical formula (i). y The preferred range of f is the same as that of the above zirconium oxide composition. y same.

[0113] The crystal system of zirconium oxide in the calcined zirconium oxide of the present disclosure also depends on the firing temperature when the calcined zirconium oxide is produced, and is generally considered to be less than the proportion of the monoclinic system in the zirconium oxide composition before the calcined zirconium oxide is produced. m The total amount of monoclinic, tetragonal and cubic crystals is preferably 60% or more, more preferably 70% or more, further preferably 80% or more, further preferably 90% or more, and particularly preferably 95% or more.

[0114] In order to ensure sufficient strength for machining, the zirconia calcined body of the present disclosure preferably has a bending strength of 15 MPa or more measured in accordance with ISO 6872:2015. In addition, in order to facilitate machining, the bending strength is preferably 70 MPa or less, and more preferably 60 MPa or less.

[0115] The zirconia calcined body of the present disclosure may contain the additives described above for the zirconia composition.

[0116] The zirconia calcined body of the present disclosure may be a molded body having a predetermined shape (hereinafter referred to as a "second molded body"). For example, the zirconia calcined body may have a disk (circular plate) shape, a rectangular parallelepiped shape, or a dental product shape (e.g., a crown shape). Dental products (e.g., crown-shaped restorations) obtained by processing a calcined zirconia disk using a CAD / CAM (Computer-Aided Design / Computer-Aided Manufacturing) system are also included in the calcined body.

[0117] The zirconia calcined body disclosed herein is produced so that the shrinkage rate changes less than that of the zirconia composition as described above. Therefore, the zirconia calcined body disclosed herein can make the shrinkage rate from the calcined body to the sintered body equal, and can produce a zirconia sintered body with high dimensional accuracy.

[0118] According to the zirconia calcined body of the present disclosure, as described above, a zirconia sintered body with high light transmittance can be produced even with a short sintering time. That is, the zirconia calcined body of the present disclosure has the advantage associated with the short sintering time described above.

[0119] Next, an example of a method for producing a zirconia calcined body according to the present disclosure will be described.

[0120] The zirconia calcined body disclosed in the present invention can be produced by sintering (i.e., calcining) the pressurized compact (first compact) produced in the above-mentioned first forming step at a temperature at which the zirconia particles do not sinter (pre-sintering step). That is, as a method for producing the zirconia calcined body disclosed in the present invention, there can be cited a production method including a pre-sintering step of sintering the first compact at a temperature at which the zirconia particles do not sinter. The aforementioned production method may include a first forming step of forming the zirconia composition to produce the first compact. The first forming step is as described in the aforementioned zirconia composition. In order to reliably perform agglomeration, the sintering temperature is, for example, preferably 800°C or more, more preferably 900°C or more, and further preferably 950°C or more. In addition, in order to improve dimensional accuracy, the sintering temperature is, for example, preferably below 1200°C, more preferably below 1150°C, and further preferably below 1100°C. In particular, in the calcining step, it is preferred that the pressed compact (first compact) made of the zirconium oxide composition of the present disclosure is calcined at 800 to 1200° C. to produce a calcined zirconium oxide body.

[0121] The method for producing a calcined zirconium oxide body of the present invention may further include, before the first forming step, a pulverizing step of pulverizing a mixture of the zirconium oxide powder and the stabilizer to obtain a zirconium oxide composition in such a manner that the zirconium oxide powder contains zirconium oxide particles having an average particle size of more than 0.17 μm and less than 0.4 μm. The pulverizing step is the same as the first pulverizing step. Furthermore, the method for producing a calcined zirconium oxide body of the present invention may further include a second pulverizing step in addition to or instead of the first pulverizing step. The second pulverizing step is as described above.

[0122] In addition, the method for producing a calcined zirconium oxide body of the present invention may further include a drying step of forming the zirconium oxide composition into particles by spray drying before the first forming step. The drying step is the same as the first drying step. Furthermore, the method for producing a calcined zirconium oxide body of the present invention may further include a second drying step in addition to or instead of the first drying step. The second drying step is as described above.

[0123] The zirconia calcined body of the present invention can be formed before the sintering step described later to produce a second formed body (second forming step). The forming method is not limited to a specific method, and a suitable method can be appropriately selected according to the purpose. For example, a zirconia disk, which is also a zirconia calcined body, can be cut into the shape of a dental product (e.g., a crown-shaped restoration) using a CAD / CAM system to produce a second formed body.

[0124] According to the above-mentioned manufacturing method, the zirconia calcined body of the present disclosure can be manufactured. As a suitable manufacturing method of the zirconia calcined body, there can be cited a manufacturing method that can manufacture a zirconia calcined body with a small change in shrinkage rate and / or a manufacturing method that can manufacture a zirconia calcined body that can be sintered in a short time. The change in shrinkage rate can be suppressed by adjusting the above-mentioned speed change temperature, selecting according to the main crystal system of zirconia, etc. The short-time sintering can be achieved by reducing the presence rate of the above-mentioned undissolved yttrium oxide f y The adjustment can be made by adjusting or selecting the average particle size of the zirconium oxide powder, etc.

[0125] Next, the zirconia sintered body disclosed in the present invention is described. The sintered body in the present invention refers to: for example, a substance in which zirconium oxide particles (powder) are not in a sintered state. The relative density of the zirconia sintered body disclosed in the present invention is preferably 99.5% or more. The relative density can be calculated in the form of a ratio of the measured density measured by the Archimedean method to the theoretical density. The relative density refers to: for a molded body in which zirconium oxide particles or granules are filled into a specific mold and formed into a specific shape by pressure, the density d1 of the sintered body obtained by sintering the aforementioned molded body at a high temperature is divided by the theoretical (internal non-voided) zirconium oxide density d2.

[0126] The zirconia sintered body disclosed in the present invention includes not only a sintered body obtained by sintering formed zirconia particles under normal pressure or without pressure, but also a sintered body densified by a high temperature pressurization treatment such as HIP (Hot Isostatic Pressing) treatment.

[0127] The preferred range of the content of the stabilizer in the zirconia sintered body of the present invention is the same as the content in the above-mentioned zirconia composition and / or zirconia calcined body. In addition, regarding the crystal system of zirconia in the zirconia sintered body of the present invention, the proportion of the monoclinic system is m The content of the monoclinic crystal, tetragonal crystal, and cubic crystal is preferably 10% or less, more preferably 5% or less, and even more preferably substantially free (0%).

[0128] Regarding the solid solution ratio of the stabilizer in the zirconia sintered body of the present disclosure, preferably 95% or more of the stabilizer is solid-dissolved in the zirconia, and more preferably substantially all of the stabilizer is solid-dissolved. When the stabilizer is yttrium oxide, the existence ratio of the undissolved yttrium oxide is f y It is preferably 5% or less, more preferably 1% or less, and even more preferably substantially all of it is dissolved in solid (0%).

[0129] From the viewpoint of masking the color of the discolored abutment, the light transmittance (ΔL * (WB)) is preferably 11 or less, more preferably 9 or less, and further preferably 7 or less. The light transmittance (ΔL * (WB)) means: About L * a * b * L of chroma (color space) in the color system (JIS Z 8781-4:2013) * The L value is measured by setting the background of the sample (sintered body) with a thickness of 1.2 mm to white. * The value is recorded as the first L * Value, for the determination of the first L * The same sample after the value is set to black and the L value is measured * The value is recorded as the second L * value, by the first L * Value minus the second L * The value obtained by the method of preparing the sample can be obtained by first pressing the zirconium oxide composition (e.g., particles) in such a way that the thickness of the sintered body reaches 1.2 mm, and then forming a circular plate-shaped body with a diameter of 19 mm by CIP forming. Then, the formed body can be fired under the prescribed firing conditions to produce a sintered body with a thickness of 1.2 mm as the sample. * The value can be determined by applying the contact liquid on the surface of the sample and then using a colorimeter (e.g., dental colorimeter "Crystalline CE100-DC / JP" (manufactured by Orinpass Co., Ltd.), analysis software "Crystalline" (manufactured by Orinpass Co., Ltd.)) to measure the L values ​​of the black background and the white background. * The white background refers to the white part of the shielding test paper described in Section 1, Part 4 of JIS K 5600-4-1:1999, and the black background refers to the black part of the shielding test paper. As the contact liquid, for example, a liquid having a refractive index nD of 1.60 measured at a measurement wavelength of 589 nm (sodium D-ray) can be used.

[0130] Regarding the light transmittance of the zirconia sintered body of the present disclosure, the light transmittance (the difference between the measured value under the white background and the measured value under the black background, hereinafter also referred to as “ΔL * (30)”) and in the above ΔL * The light transmittance of the sintered body obtained by sintering for 120 minutes at the same temperature as the maximum sintering temperature of (30) (the difference between the measured value under the white background and the measured value under the black background, hereinafter also referred to as "ΔL * (120)”) ratio ΔL * (30) / ΔL * (120) is preferably 0.88 or more. From the viewpoint of having high hiding power and good color rendering and being able to be suitably used as a dental restoration in the dental treatment of patients with abutment teeth that have discolored due to lesions or lifestyle habits, it is more preferably 0.90 or more, and even more preferably 0.95 or more.

[0131] The zirconia sintered body of the present disclosure may contain the additives described above similarly to the zirconia composition.

[0132] The zirconia sintered body of the present disclosure may be a molded body having a predetermined shape (hereinafter referred to as a "third molded body"). For example, the sintered body may have a disk (circular plate) shape, a rectangular parallelepiped shape, or a dental product shape (eg, a crown shape).

[0133] In the zirconia sintered body disclosed in the present invention, from the viewpoint of achieving good color development, the chroma C * It is preferably 3 or more, more preferably 5 or more, and even more preferably 7 or more. * The definition and determination method of chromaticity C of zirconium oxide sintered body are as described above for zirconium oxide composition. * The calcination temperature and calcination time are not particularly limited.

[0134] Next, an example of a method for producing a zirconia sintered body according to the present disclosure will be described.

[0135] The zirconia sintered body disclosed in the present invention can be produced by sintering the zirconia composition (including the first molded body) and / or the zirconia calcined body (including the second molded body) disclosed in the present invention at a temperature above the temperature at which the zirconia particles are sintered (a temperature at which sintering is possible) (sintering process). As a certain embodiment, a method for producing a zirconia sintered body including a sintering process of sintering the aforementioned first molded body at a temperature at which sintering is possible can be listed. The aforementioned production method may include a first molding process of molding the zirconia composition to produce the first molded body. The first molding process is as described in the aforementioned zirconia composition. The temperature at which sintering is possible is, for example, preferably above 1400°C, and more preferably above 1450°C. In addition, the temperature at which sintering is possible is, for example, preferably below 1650°C, and more preferably below 1600°C. The highest sintering temperature in the sintering process is preferably above 1400°C, and more preferably above 1450°C. The highest sintering temperature included in the temperature at which sintering is possible is preferably below 1650°C, and more preferably below 1600°C. The heating rate and the cooling rate are preferably below 300°C / min. Before the sintering step, a calcining step may be further included in which the first molded body is calcined at a temperature at which the zirconium oxide particles are not sintered to produce a calcined zirconium oxide body. The calcining step is as described in the method for producing a calcined zirconium oxide body. In addition, as a method for producing a sintered zirconium oxide body, before the sintering step, a second molding step may be further included in which the calcined zirconium oxide body is molded to produce a second molded body. In the case of including the second molding step, the method for producing a sintered zirconium oxide body includes: in the sintering step, the second molded body is calcined as the calcined zirconium oxide body.

[0136] In the sintering process, the holding time at a temperature (especially the maximum firing temperature) that can be sintered is preferably less than 120 minutes. From the viewpoint of being able to shorten the firing time and being able to produce dental products with high concealing properties and good color development, it is more preferably less than 90 minutes, more preferably less than 75 minutes, more preferably less than 60 minutes, particularly preferably less than 45 minutes, and most preferably less than 30 minutes. The holding time is preferably more than 1 minute, more preferably more than 5 minutes, and more preferably more than 10 minutes. According to the manufacturing method of the zirconia sintered body disclosed in the present invention, even with such a firing time, the light transmittance of the produced zirconia sintered body can be suppressed from decreasing. In addition, by shortening the firing time, it is possible to reduce energy costs while improving production efficiency.

[0137] The zirconia sintered body of the present invention can be formed to produce a third formed body (third forming step). The forming method is not limited to a specific method, and a suitable method can be appropriately selected according to the purpose. For example, a zirconia agglomerate, which is also a zirconia sintered body, can be cut into the shape of a dental product (e.g., a crown-shaped restoration) using a CAD / CAM system to produce the third formed body.

[0138] The zirconia sintered body disclosed in the present invention can be suitably used as a dental product. The zirconia sintered body can have, for example, a crown shape. As a dental product in the present invention, it can further include a porcelain material stacked on the zirconia sintered body. The porcelain material can be set as a ceramic such as a glass material. As dental products, for example, dental restorations (such as ceramic frames, full-contour crowns), orthodontic products (such as orthodontic brackets), and dental implant products (such as dental implant bridges) can be listed.

[0139] Next, the method for manufacturing the dental product of the present disclosure is described. The dental product can be manufactured by sintering the zirconium oxide composition (including the first molded body) and / or the zirconium oxide calcined body (including the second molded body) of the present disclosure having a predetermined shape. In addition, the dental product can also be manufactured by cutting the zirconium oxide sintered body of the present disclosure (including the third molded body).

[0140] When the dental product of the present disclosure has a ceramic material, it can be produced by, for example, applying a slurry containing the ceramic material to a zirconia sintered body, and firing the zirconia sintered body coated with the ceramic material to sinter the ceramic material to the sintered body. The temperature and time for sintering the ceramic material can be appropriately set.

[0141] According to the zirconium oxide composition, zirconium oxide calcined body and / or zirconium oxide sintered body of the present disclosure, a dental product with high dimensional accuracy can be obtained and / or a dental product with high hiding power and good color development can be produced in a short time.

[0142] Hereinafter, embodiments of the present disclosure will be described, but the present disclosure is not limited to the embodiments described below. Example

[0143] [Preparation of Zirconium Oxide Composition]

[0144] (Examples 1 to 3)

[0145] First, in a manner such as that described in Table 1, 100% monoclinic zirconium oxide powder is mixed with yttrium oxide to make a mixture (mixing process). Then, the mixture is added to water to make a slurry, and the average particle size (primary particle) of the zirconium oxide particles reaches 0.20 μm with a ball mill. Then, after adding a binder to the pulverized slurry, it is dried with a spray dryer to make a zirconium oxide composition. Then, in the same manner as the above method, nickel oxide (II) (NiO) is wet-pulverized with a ball mill until the average particle size reaches 0.20 μm, and NiO powder is dried with a spray dryer. NiO powder is added to the above-mentioned zirconium oxide composition at a ratio of 0.02% by mass, and the material obtained by sufficient mixing is used as the zirconium oxide composition described in Examples 1 to 3. The average particle size can be measured on a volume basis using a laser diffraction particle size distribution analyzer (SALD-2300: manufactured by Shimadzu Corporation) using a 0.2% sodium hexametaphosphate aqueous solution as a dispersion medium.

[0146] (Comparative Examples 1 to 3)

[0147] As a comparative example, a commercially available partially stabilized zirconium oxide powder was used. The zirconium oxide composition described in Comparative Example 1 is a substance obtained by adding 0.02 mass % of the NiO powder produced in Examples 1 to 3 to TZ-3YSB-E manufactured by Tosoh Corporation and mixing them thoroughly. Similarly, the zirconium oxide composition described in Comparative Example 2 is a substance obtained by adding 0.02 mass % of the above-mentioned NiO powder to Zpex manufactured by Tosoh Corporation and mixing them thoroughly, and the zirconium oxide composition described in Comparative Example 3 is a substance obtained by adding 0.02 mass % of the above-mentioned NiO powder to Zpex Smile manufactured by Tosoh Corporation and mixing them thoroughly.

[0148] (Example 4)

[0149] To the zirconium oxide composition containing monoclinic zirconium oxide powder and yttrium oxide prepared in the same manner as in Example 1, the zirconium oxide composition of Comparative Example 1 was added, and then 0.02 mass % of NiO powder prepared in Examples 1 to 3 was added and mixed thoroughly to obtain the zirconium oxide composition described in Example 4. The ratio of monoclinic crystals in the zirconium oxide composition was lower than that in Examples 1 to 3. In Table 1, the average particle size of the zirconium oxide particles contained in the zirconium oxide composition described in Comparative Example 1 could not be measured, and therefore, "NA" is indicated for this portion.

[0150] (Comparative Example 4)

[0151] The zirconium oxide composition before adding the NiO powder was pulverized so that the average particle size of the pulverized zirconium oxide particles became 0.12 μm, and a zirconium oxide composition described in Comparative Example 4 was prepared in the same manner as in Example 1.

[0152] (Comparative Example 5)

[0153] The zirconium oxide composition before adding the NiO powder was pulverized so that the average particle size of the pulverized zirconium oxide particles became 0.50 μm, and a zirconium oxide composition described in Comparative Example 5 was prepared in the same manner as in Example 1.

[0154] [Confirmation of the Existence Ratio of Undissolved Yttria and the Ratio of Crystalline System of Zirconia]

[0155] XRD measurement was performed on the zirconium oxide compositions described in the examples and comparative examples, and f, which represents the existence rate of undissolved yttrium oxide, was calculated according to the above mathematical formula (i). y In addition, f representing the ratio of monoclinic crystals in zirconium oxide is calculated according to the above mathematical formula (ii). m The results are shown in Table 1.

[0156] [Measurement of light transmittance and color development relative to firing time]

[0157] The zirconium oxide composition disclosed in the present invention was used to prepare a zirconium oxide sintered body, and the relationship between the light transmittance and the color development with respect to the holding time at the firing temperature (firing time) was investigated. First, the zirconium oxide composition described in the examples and comparative examples was heated at 300 kg / cm2 to obtain a zirconium oxide sintered body having a thickness of 1.2 mm. 2 Next, the pressed body was pressed at 1700 kg / cm 2 The CIP treatment is further performed to produce the first molded body mentioned above. The first molded body is fired at 1000°C for 2 hours to produce a zirconia calcined body. The maximum firing temperature is set to 1550°C, and the holding time at the maximum firing temperature is set to 120 minutes. The obtained zirconia calcined body is fired to produce a zirconia sintered body. Next, for the zirconia calcined body produced by the same method, the maximum firing temperature is set to 1550°C, and the holding time at the maximum firing temperature is changed to 30 minutes to produce a zirconia sintered body. The obtained zirconia sintered body is used as a sample, and the light transmittance and chroma C are measured by the method described below. * The results are shown in Table 1.

[0158] Light transmittance: L * a * b * L of chroma (color space) in the color system (JIS Z 8781-4:2013)* The value is used to calculate the L * The value was measured using a colorimeter (dental colorimeter "Crystalline CE100-DC / JP" (7-segment LED illumination, diffuse reflection type with 45° incidence, manufactured by Orinpass), analysis software "Crystalline" (manufactured by Orinpass)). The L value was measured with the background of the sintered sample set to white. * The value is recorded as the first L * Value, for the determination of the first L * The same sample after the value is set to black and the L value is measured * The value is recorded as the second L * value, will be determined by the first L * Value minus the second L * The value obtained by * (WB) is a numerical value indicating light transmittance (n=1). A contact liquid having a refractive index nD of 1.60 is applied to the measurement surface of the sample. The white background refers to the white portion of the shielding test paper described in Section 1, Part 4 of JIS K 5600-4-1:1999, and the black background refers to the black portion of the aforementioned shielding test paper.

[0159] Chroma C * Use a black background * Value and b * The value is calculated for each sample by the above mathematical formula (iii) (n=1), and the a * Value and b * The values ​​were measured using a colorimeter (dental colorimeter "Crystalline CE100-DC / JP" (7-segment LED illumination, diffuse reflection type with 45° incidence, manufactured by Orinpass), analysis software "Crystalline" (manufactured by Orinpass)). A contact liquid having a refractive index nD of 1.60 was applied to the measurement surface of the sample.

[0160] [Table 1]

[0161]

[0162] First, the zirconium oxide composition is described. In the zirconium oxide composition containing zirconium oxide powder as a commercial product described in Comparative Examples 1 to 3, the crystal system of zirconium oxide is basically tetragonal and / or cubic, and the monoclinic system is about 52% at most. In addition, in the zirconium oxide composition described in Comparative Examples 1 to 3, no XRD peak of yttrium oxide is confirmed. Therefore, it can be considered that yttrium oxide is completely dissolved in zirconium oxide.

[0163] On the other hand, in Examples 1 to 3, the crystal system of zirconium oxide was 100% monoclinic. In Example 4, since a portion of partially stabilized zirconium oxide containing a tetragonal crystal system of zirconium oxide powder as a commercial product was added, about 76% was monoclinic. In addition, in Examples 1 to 4 and Comparative Examples 4 and 5, XRD peaks of yttrium oxide were observed. In Examples 1, 4 and Comparative Examples 4 and 5, which had low yttrium oxide contents, the XRD peaks of yttrium oxide were 100% monoclinic. y In addition, in Examples 2 to 3 where the yttrium oxide content is as high as 5 to 6 mol%, y In the range of more than 7% and less than 10%.

[0164] Next, the zirconia sintered body is described. In Examples 1 to 4, the light transmittance is less than 11 when fired for 120 minutes and when fired for 30 minutes, and the chromaticity is C * All above 3. In addition, C * (30) / C * The value of (120) also shows a high value of 0.97 or more, and thus, the masking property and color development are sufficient even with a short firing time. Therefore, in dental treatment, it is possible to obtain good color development with a short firing time, and mask the color of the abutment teeth that have changed color due to pathological changes or coloring caused by lifestyle habits.

[0165] On the other hand, in Comparative Examples 1 to 3, the light transmittance was less than 11 when fired for 120 minutes and 30 minutes, but the chroma C * Less than 3,C after 30 minutes of firing * (30) / C * The value of (120) is also as low as 0.40 or less, and therefore, a desired color cannot be achieved by firing for a short time.

[0166] The light transmittance of Comparative Example 4 was too high and the shielding property was insufficient. * (30) / C * The value of (120) was also slightly lower than that of Examples 1 to 3, and the color development during short-time firing was also poor.

[0167] In Comparative Example 5, a dense zirconia sintered body could not be produced when the sintering was performed for 120 minutes or 30 minutes.

[0168] Industrial Applicability

[0169] The zirconium oxide composition, zirconium oxide calcined body and zirconium oxide sintered body disclosed in the present invention, and the method for producing the same can be used in various applications such as dental products such as dental restorations, optical fiber connection parts such as metal nozzles (ferrules) and sleeves, various tools (such as grinding balls and grinding tools), various parts (such as screws, bolts and nuts), various sensors, electronic parts, decorative items (such as watch bands), etc. When the composition, calcined body and sintered body are used as dental materials, they can be used for copings, frameworks, crowns, crown bridges, abutments, implants, implant screws, implant fixtures, implant bridges, implant bars, brackets, dentures, inlays, onlays, orthodontic wires, laminated veneers, etc.

Claims

1. A zirconium oxide composition comprising a zirconium oxide powder and a stabilizer capable of inhibiting phase transformation of the zirconium oxide powder, and satisfying all of the following (1) to (3): (1) The zirconium oxide powder contains zirconium oxide particles having an average particle size of more than 0.17 μm and less than 0.3 μm; (2) At least a portion of the stabilizer is not dissolved in zirconium oxide; (3) When the composition is fired at 1300 to 1600°C, the chromaticity C of the sintered body when it is kept at the temperature for 30 minutes is * (30) and the chromaticity C of the sintered body when it is kept at the above temperature for 120 minutes * (120) ratio C * (30) / C * (120) is greater than 0.

4.

2. The zirconium oxide composition according to claim 1, wherein The monoclinic system in the crystal system of zirconium oxide accounts for 55% or more.

3. The zirconium oxide composition according to claim 1 or 2, wherein The stabilizer is yttrium oxide.

4. The zirconium oxide composition according to claim 3, wherein The yttrium oxide is contained in an amount of 3 to 7.5 mol% based on the total mole of zirconium oxide and yttrium oxide.

5. The zirconium oxide composition according to claim 3, wherein In the X-ray diffraction pattern, there is a peak of yttrium oxide.

6. The zirconium oxide composition according to claim 3, wherein The existence ratio f of yttrium oxide not dissolved in zirconium oxide is calculated by the following mathematical formula (i): y More than 1%, [Mathematical formula 1] Among them, I y (111) represents the peak intensity of the (111) plane of yttrium oxide at around 2θ=29° in the X-ray diffraction pattern using CuKα rays; I m (111) and I m (11-1) represents the peak intensity of the (111) plane and the (11-1) plane of the monoclinic system of zirconium oxide in the X-ray diffraction pattern; I t (111) represents the peak intensity of the (111) plane of the tetragonal system of zirconium oxide in the X-ray diffraction pattern; I c (111) represents the peak intensity of the (111) plane of the cubic crystal system of zirconium oxide in the X-ray diffraction pattern.

7. The zirconium oxide composition according to claim 6, wherein The f y Less than 15%.

8. The zirconium oxide composition according to claim 1 or 2, wherein: The chroma C of the sintered body when kept at the above temperature for 30 minutes * (30) is 3 or more.

9. The zirconium oxide composition according to claim 1 or 2, wherein: The light transmittance of the sintered body obtained by sintering at a maximum sintering temperature of 1300 to 1600° C. satisfies the following formula: ΔL * (W-B)≤11 In the formula, ΔL * (WB) is the first L * Value minus the second L * The value obtained by the first L * The value is L measured with the background of the sintered body of 1.2 mm thickness set to white. * Value, second L * The value will be determined for the first L * The L value of the same sintered body is measured with the background set to black. * Value, L * The value is L according to JIS Z 8781-4:2013 * a * b * The chroma L in the color system * value.

10. The zirconium oxide composition according to claim 9, wherein Light transmittance ΔL when kept at the temperature for 30 minutes * (30) and the light transmittance ΔL when kept at the temperature for 120 minutes * (120) ratio ΔL * (30) / ΔL * (120) is greater than 0.

88. 11 . A method for producing a calcined zirconium oxide body, comprising producing the calcined zirconium oxide body using the zirconium oxide composition according to claim 1 .

12. The method for producing a zirconia calcined body according to claim 11, wherein: The press-formed body comprising the zirconium oxide composition according to any one of claims 1 to 10 is sintered at 800 to 1200°C to produce the pressed body.

13. The method for producing a zirconia calcined body according to claim 11 or 12, comprising: A first molding step of molding a zirconium oxide composition comprising a zirconium oxide powder and a stabilizer capable of suppressing phase transformation of the zirconium oxide powder according to any one of claims 1 to 10 to produce a first molded body; and The first molded body is sintered at a temperature at which the zirconium oxide particles are not sintered.

14. The method for producing a zirconia calcined body according to claim 13, wherein: In the calcining step, the first compact is calcined at 800 to 1200°C.

15. The method for producing a zirconia calcined body according to claim 13, wherein: Before the first forming step, the method further includes: grinding a mixture of the zirconium oxide powder and the stabilizer to obtain a zirconium oxide composition in a manner that the zirconium oxide powder includes zirconium oxide particles having an average particle size of more than 0.17 μm and less than 0.3 μm.

16. The method for producing a zirconia calcined body according to claim 13, wherein: Before the first forming step, the method further includes a drying step of forming the zirconium oxide composition into particles by spray drying.

17. The method for producing a zirconia calcined body according to claim 11, wherein: The density of calcined zirconium oxide is 2.7~4.0g / cm 3 .

18. The method for producing a zirconia calcined body according to claim 11, wherein: The flexural strength of the zirconia calcined body measured in accordance with ISO6872:2015 is 15 to 70 MPa.

19. A method for producing a zirconia sintered body, comprising: A first forming step of forming a first formed body by forming the zirconium oxide composition according to any one of claims 1 to 10; as well as The sintering step is to sinter the first compact at a temperature higher than a sinterable temperature.

20. The method for producing a zirconia sintered body according to claim 19, wherein: Before the sintering step, the method further includes: sintering the first molded body at a temperature at which zirconium oxide particles are not sintered to produce a zirconia calcined body; in the sintering step, the zirconia calcined body is sintered as the first molded body.

21. The method for producing a zirconia sintered body according to claim 20, wherein: Before the sintering step, the method further includes: forming the zirconia calcined body to produce a second formed body; In the sintering step, the second compact is sintered.

22. The method for producing a zirconia sintered body according to any one of claims 19 to 21, wherein: In the sintering step, the holding time at the maximum sintering temperature is 1 hour or less.

Citation Information

Patent Citations

  • Light-transmitting sintered zirconia compact, method for producing the same, and use thereof

    JP2009269812A

  • Translucent zirconia sintered body and zirconia powder, and use therefor

    CN105829264A

  • Zirconia fine powder and production method therefor

    CN108137342A

  • Zirconia composition, pre-calcined object and sintered compact, and method for producing same

    CN109689593A